Evaluating the Validity and Reliability of a Student Self-Advocacy Teacher Rating Scale - Walick, Christopher M. (Journal of the American Academy of Special Education Professionals, 2017)
Self-advocacy skills are critical to high school and post-secondary success. Unfortunately, students with disabilities often times struggle with self-advocacy. While there are effective, evidence-based programs to teach self-advocacy skills, there are few scales that directly measure self-advocacy. The current research study was conducted to develop and evaluate a valid and reliable self-advocacy teacher-report scale. The scale was developed, piloted, and evaluated with high school students with disabilities. The study results from the study indicate that the self advocacy scale is a valid and reliable measure of a student’s self-advocacy behavior, and that the scale help explain a notable amount of variation of classroom success. Implications, future research and limitations are discussed.